Efektivitas Progressive Muscle Relaxation Therapy Terhadap Penurunan Tekanan Darah Sistolik pada Wanita Lanjut Usia dengan Hipertensi Primer - Dini Afriani Khasanah; Isnaini Herawati (Prosiding University Research Colloquium, 2018)
Elderly, especially women have decreased the function of one of themon the circulatory system. The occurrence of decreased elasticity ofblood vessel wall is one cause of the increase in blood pressure,especially systolic blood pressure. One of the treatment efforts done isprogressive muscle relaxation therapy. It aims to elicit a relaxedresponse to affect the systemic and pulmonary circulation in order todecrease systolic blood pressure. The purpose of this study was toinvestigate the effectiveness of progressive muscle relaxation therapyto decrease systolic blood pressure in elderly women with primaryhypertension. The type of research used is Quasi Experimental Designwith Pretest-Posttest With Control Group Design research design. Thenumber of respondents is 19 people. The results of this study showed adecrease in systolic blood pressure of 7 mmHg in the control groupand 20 mmHg in the treatment group. Indenpedent test results obtainedsystolic blood pressure value is p value (0.003 <0.05).